Digital Electrochemistry for On‐Chip Heterogeneous Material Integration. Issue 26 (24th May 2021) - Bao, Bin; Rivkin, Boris; Akbar, Farzin; Karnaushenko, Dmitriy D.; Bandari, Vineeth Kumar; Teuerle, Laura; Becker, Christian; Baunack, Stefan; Karnaushenko, Daniil; Schmidt, Oliver G.
Abstract: Many modern electronic applications rely on functional units arranged in an active‐matrix integrated on a single chip. The active‐matrix allows numerous identical device pixels to be addressed within a single system. However, next‐generation electronics requires heterogeneous integration of dissimilar devices, where sensors, actuators, and display pixels sense and interact with the local environment. Heterogeneous material integration allows the reduction of size, increase of functionality, and enhancement of performance; however, it is challenging since front‐end fabrication technologies in microelectronics put extremely high demands on materials, fabrication protocols, and processing environments. To overcome the obstacle in heterogeneous material integration, digital electrochemistry is explored here, which site‐selectively carries out electrochemical processes to deposit and address electroactive materials within the pixel array. More specifically, an amorphous indium‐gallium‐zinc oxide (a‐IGZO) thin‐film‐transistor (TFT) active‐matrix is used to address pixels within the matrix and locally control electrochemical reactions for material growth and actuation. The digital electrochemistry procedure is studied in‐depth by using polypyrrole (PPy) as a model material. Active‐matrix‐driven multicolored electrochromic patterns and actuator arrays are fabricated to demonstrate the capabilities of this approach for material integration. The approach can be extended to a broad range of materials and structures, opening up a new path for advanced heterogeneous microsystem integration. Abstract : A novel digital electrochemistry approach is proposed, which site‐selectively carries out electrochemical reactions to deposit electroactive materials. Multicolored electrochromic patterns and actuator arrays are fabricated. The approach can be extended to a broad range of materials and structures, opening up a new path for advanced heterogeneous microsystem integration.